Degradation Mode of PBAT Mulching Film and Control Methods During its Degradation Induction Period - Qiao, Runmeng; Wang, Xin; Qin, Guangjiong; Liu, Jialei; Cao, Aocheng; Ouyang, Canbin; He, Wenqing (Mini-Reviews in Organic Chemistry, 2022)
Plastic films play an important role in China's agricultural production. However, the large-scale use of plastic film has also caused very serious agricultural film pollution. Biodegradable polymers have received much attention because of the environmental pollution caused by the traditional plastic mulching film. The most typical copolymer is poly (butylene adipate co butylene terephthalate) (PBAT). Poly (Butylene Adipate-co-Terephthalate) (PBAT) is a kind of aliphaticaromatic polyester with excellent biodegradability and mechanical processing properties. Therefore, it has been rapidly developed and widely used in the industry. However, the degradation period of the agricultural film depends on certain requirements. Currently, the degradable materials available in the market do not meet the needs of all crops due to their degradation period. In this paper, the basic properties, degradation process and methods to delay the degradation of PBAT are reviewed for improving the degradation period of the plastic film that is prepared by using this kind of material. The degradation process includes photodegradation, biodegradation, and hydrolysis. The methods of delaying the degradation process include adding a chain extender, light stabilizer, antihydrolysis agent and antibacterial agent, providing a theoretical basis for the research and development of biodegradable film with a controllable degradation cycle. The future research and development of biodegradable polymers will mainly focus on controllable degradation rate, stable degradation cycle, new materials, and reducing research and development costs.
Keywords: biodegradable plastic film